2019
DOI: 10.1101/671073
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting of the dosage-compensated male X-chromosome during earlyDrosophiladevelopment

Abstract: The essential process of dosage compensation, which corrects for the imbalance in Xlinked gene expression between XX females and XY males, represents a key model for how genes are targeted for coordinated regulation. However, the mechanism by which dosage compensation complexes identify the Xchromosome during early development remained unknown because of the difficulty of sexing embryos prior to zygotic transcription. We used meiotic drive to sex Drosophila embryos prior to zygotic transcription and ChIPseq to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In addition to GAF and Zld, the transcription factor CLAMP is expressed in the early embryo and functions in chromatin accessibility and transcriptional activation (Rieder et al 2017;Soruco et al 2013;Urban et al 2017aUrban et al , 2017bRieder et al 2019). While CLAMP, like GAF, binds GAdinucleotide repeats, the two proteins preferentially bind to slightly different GA-repeats (Kaye et al 2018).…”
Section: Maternally Encoded Gaf Is Essential For Development Beyond Tmentioning
confidence: 99%
“…In addition to GAF and Zld, the transcription factor CLAMP is expressed in the early embryo and functions in chromatin accessibility and transcriptional activation (Rieder et al 2017;Soruco et al 2013;Urban et al 2017aUrban et al , 2017bRieder et al 2019). While CLAMP, like GAF, binds GAdinucleotide repeats, the two proteins preferentially bind to slightly different GA-repeats (Kaye et al 2018).…”
Section: Maternally Encoded Gaf Is Essential For Development Beyond Tmentioning
confidence: 99%
“…Sxl regulation of msl-2 RNA splicing and stability links the sex determination pathway to another important early embryonic event: dosage compensation, which equalizes gene dosage of X-linked genes between females with two X-chromosome and males with a single X-chromosome. MSL-2 is an essential core component of the MSL complex, present only in the male embryo and responsible for dosage compensation (Prayitno et al 2019; Rieder et al 2019). The binding of Sxl to the msl-2 transcript specifically in females results in skipping of the first exon in females, thereby hindering translation of the protein, which prevents MSL complex formation in females and allows it to be formed only in males (Gebauer et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Most HASs contain low-complexity GAGA motifs, referred to as the MRE (19,56). The CLAMP protein binds to MREs and is responsible for chromatin opening (28,92). Some C2H2 proteins that interact with MSL1 can functionally cooperate with CLAMP and bind to HASs.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with previous findings that the N-terminal 265 aa of MSL1, in cooperation with MSL2 and possibly with MLE, but not with MSL3 and MOF, can specifically bind to several sites on female polytene chromosomes (30). Rieder et al (92) showed that at the initiation of embryogenesis, the DCC first binds to all chromosomes before becoming concentrated on the X chromosome. Weak interactions with chromatin sites on autosomes likely lead to the rapid dissociation of the DCC, resulting in the gradual concentration of the DCC on HASs.…”
Section: Discussionmentioning
confidence: 99%